Inovasi Produk Olahan Abon Ikan Lele Halal sebagai Strategi Pemberdayaan Ekonomi di Desa Mayangan - Hidayah, Bashirotul; Ratnaningtyas, Oktavia; Halisa , Fatma Nur; Mufarikhah, Nurul; Rohima, Dina (Keris: Journal of Community Engagement, 2025)
Mayangan Village has great potential in the catfish cultivation sector; However, low selling value and dependence on local markets result in unstable farmers' incomes. This problem needs to be overcome so that the community can improve their economic welfare. Therefore, community empowerment activities are carried out through training on the processing of halal catfish shredded fish as a value-added product. The purpose of this activity is to provide skills to housewives in a hygienic production process and in accordance with halal principles, so that they can increase family income. The method used is the ABCD (Asset Based Community Development) approach, which emphasizes the utilization of local potential and active community participation. These activities include the identification of potential natural and human resources, as well as technical training in product processing and marketing. The results of this activity showed that participants were able to understand and carry out the production process of shredded catfish independently. With these new skills, it is hoped that the community can develop sustainable businesses, increase income, and expand the product market to a wider area. This program is expected to be an empowerment model that can be replicated in other areas with similar conditions.